Sexism and Misogyny in Nepali Proverbs: A Psychoanalytic Feminist Approach (Siddhajyoti Interdisciplinary Journal, 2024)
People use many Nepali-gendered proverbs in formal and informal talks. They discriminate and abuse women consciously or unconsciously in gender contexts. Gender inequality has been a challenging social problem. This study investigates the representations of the sexist, abusive and ingrained prejudices and hatred against women in Nepali Proverbs. It analyses the perceptions and psyche of patriarchy towards Nepali women. This study adopted psychoanalytic feminist theory to analyse sexism and misogyny in Nepali proverbs. Nepali proverbs related to gender discrimination were selected from different written sources. The collected proverbs were presented from the birth of a girl to young, widowhood and old age. The discussed proverbs vividly illustrate prevalent prejudice, discrimination, stereotyping, hatred and contempt against women in Nepali society. These gendered proverbs disclose the discrimination and prejudice on gender issues from birth onwards. The proverbs expose the men’s negative and aversive attitude, assumptionsand psyche towards women. Patriarchal ideology determines ‘good women’ or ‘bad women’; men and patriarchal women expect women should follow the traditional gender roles. Through the gendered proverbs, the patriarchal psyche is palpable as it seeks to subjugate women. This research will aware people, especially the new generation, about the misconceptions of gender in Nepali society, and motivate them not to use those gender discriminatory proverbs for the gender equality and reverence of women.